2021
DOI: 10.1108/ir-07-2021-0139
|View full text |Cite
|
Sign up to set email alerts
|

An overview of pruning and harvesting manipulators

Abstract: Purpose The motivation for robotics research in the agricultural field has sparked in consequence of the increasing world population and decreasing agricultural labor availability. This paper aims to analyze the state of the art of pruning and harvesting manipulators used in agriculture. Design/methodology/approach A research was performed on papers that corresponded to specific keywords. Ten papers were selected based on a set of attributes that made them adequate for review. Findings The pruning manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In recent decades, researchers have put a lot of effort into harvesting robots, though only a few studies proposed design procedures based on proper mechanical design indices [20][21][22][23][24][25], and it seems others only designed their manipulators empirically and evaluated the mechanical performance to validate the design [26]. A review of harvesting and pruning robots can be found in [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, researchers have put a lot of effort into harvesting robots, though only a few studies proposed design procedures based on proper mechanical design indices [20][21][22][23][24][25], and it seems others only designed their manipulators empirically and evaluated the mechanical performance to validate the design [26]. A review of harvesting and pruning robots can be found in [27][28][29].…”
Section: Introductionmentioning
confidence: 99%